2005
DOI: 10.1016/j.jmaa.2005.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Some applications of free Fisher information on frame theory

Abstract: We introduce the notion of operator-valued free Fisher information with respect to a positive map of a random variable in an operator-valued noncommutative probability space and point out its close relations to the modular frames arising from conditional expectations. Then we can apply this notion on the study of frame theory, especially on the disjointness problem of modular frames arising from conditional expectations.  2005 Elsevier Inc. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In [10], we introduced the operator-valued free Fisher information of one variable with respect to a linear map which is a generalization of D.Shlyakhtenko's notion in [15]. Such a notion can be generalized to several random variables'setting easily.…”
Section: The Free Fisher Information Of Random Matricesmentioning
confidence: 99%
See 3 more Smart Citations
“…In [10], we introduced the operator-valued free Fisher information of one variable with respect to a linear map which is a generalization of D.Shlyakhtenko's notion in [15]. Such a notion can be generalized to several random variables'setting easily.…”
Section: The Free Fisher Information Of Random Matricesmentioning
confidence: 99%
“…In the case of states, the non-tracial framework was worked out by D. Shlyakhtenko in [17]. In [9,10], we generalized the notion of free Fisher information to the operator-valued setting and this work is done in the general von Neumann algebra framework and found that the free Fisher information of an operator-valued semicircular variable with conditional expectation covariance is closely related to modular frames.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [6], we have generalized the notion of free Fisher information to the operator-valued setting. (M, E, B) be a B-valued noncommutative probability space, and let X ∈ M be a self-adjoint random variable and η : B → B be a linear map.…”
Section: Rank Preserving Module Maps On L(h a )mentioning
confidence: 99%